Dan's days aged 11 1/2 : (being yet another week of his words) - "Flavell, Adrian" (Hawthorn; Mimosa/McGraw-Hill, 2007)
A week in the life of Dan. He's eleven and a half, in his last year of primary school, and his band has their first gig at the school dance
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Humorous fiction